An overview of behavioral disorders and its therapeutic management in Dogs and Cats - Keerthana, Aruru; Srinivasan, G; Sunilchandra, U; Shridhar, N B; Vijay Kumar, M; Ravikumar, C (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Many of the dogs and cats lives affected with behavioral disorders have been ended either in euthanasia, relinquishment, chronic suffering or would have handed over to shelters. Various types of behavioral disorders in dogs and cats include nonspecific/idiopathic aggression, fear, phobia, anxiety disorder and stereotyping behavior. The goal of therapy should be the modification of the abnormal behavior by environmental management, training with pharmacological intervention being adjunct to the behavioral modification training. Major classes of behavioral modifying drugs used in pets are selective serotonin reuptake inhibitors (SSRI), tricyclic antidepressants (TCA), monoamine oxidase inhibitors (MAOI), antipsychotic agents, anticonvulsants and benzodiazepines. The mechanism of action has been attributed to modification of the availability or function of various neurotransmitters implicated in the behavioral disorders. Presently, the approved drugs for veterinary use has been limited to: selegiline, a SSRI, for canine cognitive dysfunction and clomipramine, a TCA, for separation anxiety in dogs, with majority drugs being used on extra label fashion with the extrapolation of human data. The article reviews about the pathophysiology of behavioral disorders, diagnostic approaches and drugs available for the treatment of abnormal behavior caused by variation in neurotransmitter.